Insights of biosurfactant producing Serratia marcescens strain W2.3 isolated from diseased tilapia fish: a draft genome analysis - Chan, Xin Yue; Chang, Chien Yi; Hong, Kar Wai; Tee, Kok Keng; Yin, Wai Fong; Chan, Kok Gan (BioMed Central, 2013)
Background Serratia marcescens is an opportunistic bacterial pathogen with broad range of host ranging from vertebrates, invertebrates and plants. S. marcescens strain W2.3 was isolated from a diseased tilapia fish and it was suspected to be the causal agent for the fish disease as virulence genes were found within its genome. In this study, for the first time, the genome sequences of S. marcescens strain W2.3 were sequenced using the Illumina MiSeq platform.